Pengaruh Arus Kas Operasi,Arus Kas Bebas, Leverage Terhadap Kebijakan Dividen Dengan Profitabilitas Sebagai Variabel Intervening: (Studi Empiris Pada Perusahaan Transportasi dan Logistic 2019-2021) - Erliana Erliana (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
The purpose of this research is to test the influence of cash flow operations, free cash flows, leverage on policy dividencies with profitability as variables. Empirical study of transport and logistic companies registered in the Indonesian stock exchange, periods 2019 to 2021. In this study there are 22 companies. The sample technique used is an impressive sampling and the number of samples of 22 companies with observation years over 3 years, so the sample data after the observation became 66. The model used in this study is the regression of the data panel using the eviews application 12. Research findings is the cash flow of operations affects profitability, free cash flow has a significant impact on profitability, leverage has no direct bearing on dividends policy.